2023
DOI: 10.7717/peerj.14807
|View full text |Cite
|
Sign up to set email alerts
|

Burden in caregivers of children with congenital Zika syndrome in Pernambuco, Brazil: analysis and application of the Zarit burden interview scale

Abstract: With the increase in cases of microcephaly caused by the Zika virus, the demand for special care and a better quality of life for the child and caregiver increased proportionally. Objective This study aimed to analyze the burden on caregivers of children with congenital Zika syndrome associated with viral infections in the state of Pernambuco, Brazil using the Zarit Burden interview scale. Method A quantitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To gain insight into the caregivers' psychological well-being, we utilized the ZBI score as our primary assessment tool [ 6 ]. This tool specifically measures the physical, emotional, and financial burden experienced by caregivers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into the caregivers' psychological well-being, we utilized the ZBI score as our primary assessment tool [ 6 ]. This tool specifically measures the physical, emotional, and financial burden experienced by caregivers.…”
Section: Methodsmentioning
confidence: 99%
“…Burnout has been defined by Maslach and Jackson (1981) as a three-component syndrome: emotional exhaustion, decreased sense of personal accomplishment, and depersonalization [5]. The Zarit burden interview (ZBI) is a reliable tool frequently used to assess caregiver burnout [6]. Studies have demonstrated that caregivers of individuals with chronic illnesses experience higher rates of burnout [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such alterations can be accompanied by tooth sensitivity/pain which, in turn, may negatively impact the quality of life of these children. [9][10][11] Although previous studies have documented cases of CZS-associated microcephaly with oral manifestations in regions considered to be the epicenter of the infection, such as in the northeast of Brazil; 7,[12][13][14] the literature is very scarce in other areas such as in the southeast. 15 Furthermore, the lack of solid knowledge about the findings of rare diseases prevents progress in developing some means to reduce the burden of these conditions.…”
Section: Introductionmentioning
confidence: 99%